Effect of Mobile Application Use on Oral Hygiene among Orthodontics Users: Meta-Analysis - Dini Hapsari; Eti Poncorini Pamungkasari; Argyo Demartoto (Journal of Health Promotion and Behavior, 2024)
Background: The high prevalence of malocclusion causes the need for orthodontic treatment to increase. The results of the 2018 National Basic Health Research, the prevalence of dental and oral problems is 57.6%, especially in adolescents. Oral hygiene is an important factor that must be controlled by patients during orthodontic treatment because it can affect the quality and time of treatment. The mobile application is here to facilitate and provide optimal dental health information to orthodontic users. This study aims to analyze and estimate the influence of mobile applications on oral hygiene in orthodontic users. Subjects and Method: This study used a systematic review and meta-analysis by following PICO, Population: orthodontic patients. Interventions: mobile applications. Comparation: without a mobile application. Outcome: oral hygiene. The data used were obtained from scientific research articles from electronic databases including Pubmed, Google Schoolar, Science Direct Randomized Control Trial (RCT) designs from 2013 to 2023 which report effect sizes with Mean and SD. The keywords used are “orthodontic” AND “oral hygiene” OR “oral health” AND “mobile application” OR “app”. The selection of articles was carried out using the PRISMA flowchart. Data were analyzed using Review Manager software version 5.3. Results: A total of 9 articles with eligible RCT designs from Asia and Europe were selected for the systematic review and meta-analysis. The results of the meta-analysis showed that oral hygiene for orthodontic users who used mobile applications was better than those who did not use mobile applications, and was statistically significant (SMD= -0.59; 95% CI= -0.90 to 0.29; p= .001). Conclusion: Mobile application improves oral hygiene in orthodontic users.